Pengaruh jenis benih dan tekanan penghisap seeder automatic terhadap efisiensi penyemaian benih - chaniago, maju amanda; harahap, wahyuni umami; nordin, mohd nadzim bin (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2024)
The aim of this research is to determine the effect of seed type and automatic seeder suction pressure on seed sowing efficiency. This research was carried out at the engineering research (ER) center located in the engineering workshop, Malaysian Agricultural Research and Development Institute (MARDI) Serdang, Malaysia. With an altitude of 1,400 meters above sea level, in September 2024. This research used a non-factorial randomized block design, where each combination of seed type and suction pressure was tested three times, namely: 10 cc; 14cc; 20cc. Based on the results of tests and analysis that have been carried out on the performance of the automatic seeder for three types of seeds (chilies, shallots and cabbage) with variations in suction pressure, it has a real influence on sowing efficiency, but the influence varies depending on the type of seed. Chili seeds showed increased efficiency as suction pressure increased. 20 cc pressure gave the best results with 91.67% of seeds in the P1 category (one seed per hole). Shallot seeds show different responses to pressure variations. 14 cc pressure provides the best balance between the P1 and P>1 categories. High pressure (20 cc) causes a significant reduction in efficiency. Cabbage seeds showed consistent efficiency at low (10 cc) and high (20 cc) pressures. There is a slight decrease in efficiency at medium pressure (14 cc). Automatic seeders show significant potential to improve seeding efficiency in modern agricultural practices. However, its effectiveness is highly dependent on precise adjustments to the characteristics of the seeds used. This research highlights the importance of optimizing operational parameters of automatic seeders to maximize efficiency and productivity in the seeding process.